Extended Kalman observer based sensor fault detection - Noura Rezika Bellahsene Hatem; Mohammed Mostefai; Oum El Kheir Aktouf (Institute of Advanced Engineering and Science, 2019)
This article discusses the Kalman observer based fault detection approach. The calculation of the residues can detect faults, but if there are noises, uncertainties become very important. To reduce the influence of these noises, a calculation of the instantaneous energy of the residues gave a better precision. The Kalman observer was used to estimate system performance and eliminate unknown noise and external disturbances. Instantaneous Power Calculation (IPCFD) based fault detection can detect potential sensor faults in hybrid systems. The effectiveness of the proposed approach is illustrated by the main application.